Ekoraya: Biodiversity Flipbook Based on Science Literacy - lestari, Vadia Regitha; Khotimah , Khusnul; Iksam, Iksam; Lestari , Vadia Regitha (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
This research is motivated by the fact that scientific literacy in learning in Indonesia is still very lacking. The learning media that have been used so far are less varied and limited, teachers have also never applied learning media based on scientific literacy in the classroom. The objectives of this study are: (1) to find out the process of developing learning media, (2) to find out the feasibility of learning media and, (3) to find out the practicality of learning media. This study uses the Research and Development (RnD) method. Media development uses the ADDIE model. The subjects in this study were 27 students of grade V at SDN 007 Samarinda Ulu. Data collection techniques used interviews, questionnaires and documentation. The research instruments used were material expert feasibility assessment questionnaires, student response questionnaires and teacher response questionnaires. The results of this study were; feasibility tests by material experts of 94% with the category "Very Feasible", feasibility tests by media experts of 86% with the category "Very Feasible". Then, the assessment of media by small groups was 91.77% in the category of "Very Practical", the large group test was 88.35% in the category of "Very Practical", and the results of the media assessment by teachers were 96.47% in the category of "Very Practical" for use in learning.